Approximate Solution of Some Classes of Integral Equations Using Bernstein Polynomials of Two-Variables (Baghdad Science Journal, 2012)
The research aims to find approximate solutions for two dimensions Fredholm linear integral equation. Using the two-variables of the Bernstein polynomials we find a solution to the approximate linear integral equation of the type two dimensions. Two examples have been discussed in detail.